A randomised-controlled trial of 1-year adjuvant chemotherapy with oral tegafur–uracil versus surgery alone in stage II colon cancer: SACURA trial. (June 2018) - Matsuda, Chu; Ishiguro, Megumi; Teramukai, Satoshi; Kajiwara, Yoshiki; Fujii, Shoichi; Kinugasa, Yusuke; Nakamoto, Yoshihiko; Kotake, Masanori; Sakamoto, Yoshiyuki; Kurachi, Kiyotaka; Maeda, Atsuyuki; Komori, Koji; et al.
Abstract: Background: Efficacy of adjuvant chemotherapy in patients with stage II colon cancer is still controversial. The SACURA trial is a randomised-controlled study evaluating the superiority of 1-year adjuvant treatment with oral tegafur–uracil (UFT) to surgery alone for stage II colon cancer. Methods: Patients were randomly assigned to the surgery-alone group or UFT group (UFT at 500–600 mg/day for 5 days, followed by 2-day rest, for 1 year). The primary end-point was disease-free survival (DFS). Target sample size was 2000, determined with one-sided alpha of 0.05, power of 0.9 and assumed hazard ratio (HR) 0.729. Results: A total of 1982 patients (997 in the surgery-alone group and 985 in the UFT group) were analysed. Median follow-up was 69.5 months, median age was 66 years and for stage IIA/IIB/IIC, the distribution was 84%/13%/3%. The 5-year DFS rate was 78.4% in the surgery-alone group and 80.2% in the UFT group. The HR for DFS was 0.91 (95% confidence interval [CI], 0.75–1.10; p = 0.31); superiority of UFT was not demonstrated. Approximately 9% of patients experienced second cancers, which consist 40.7% of the DFS events. The 5-year relapse-free and overall survival rates of the surgery-alone and UFT group were 84.6% and 87.2% (HR, 0.82; 95% CI, 0.65–1.04) and 94.3% and 94.5% (HR, 0.93; 95% CI, 0.66–1.31), respectively. Subgroup analysis failed to disclose superiority in prognosis of adding UFT to the patients with risk factors for recurrence. Conclusions: Superiority of 1-year adjuvant UFT over surgery alone was not demonstrated in stage II colon cancer. Patients with risk factors for recurrence did not benefit from UFT. Trial registration: ClinicalTrials. Gov. #NCT00392899 . Highlights: SACURA is the only randomised-controlled trial focused on adjuvant therapy for stage II colon cancer. No superiority of 1-year tegafur–uracil (UFT) in survival was demonstrated in 1982 patients with stage II colon cancer. No subgroup that benefited from adjuvant chemotherapy could be identified. Subgroups with risk factors for recurrence were not the ones benefited from UFT.